Microbial evasion of the complement system: a continuous and evolving story - Heggi, Mariam T.; Nour El-Din, Hanzada T.; Morsy, Dina I.; Abdelaziz, Noha I.; Attia, Ahmed S. (Frontiers in Immunology, 2024)
The complement system is a fundamental part of the innate immune system that plays a key role in the battle of the human body against invading pathogens. Through its three pathways, represented by the classical, alternative and lectin pathways, the complement system forms a tightly regulated network of soluble proteins, membrane-expressed receptors, and regulators with versatile protective and killing mechanisms. However, ingenious pathogens have developed strategies over the years to protect themselves from this complex part of the immune system. This review will briefly discuss the sequence of the complement activation pathways. Then, we present a comprehensive updated overview of how the major four pathogenic groups: bacteria, viruses, fungi, and parasites control, modulate and block the complement attacks at different steps of the complement cascade. We shed more light on the cleverness of those pathogens in deploying more than one mechanism to tackle the complement system in their path to establish infection within the human host.